2016
DOI: 10.1007/s10157-016-1328-y
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of relapse and long-term outcome in children with steroid-dependent nephrotic syndrome after rituximab treatment

Abstract: The introduction of RTX may not be necessarily associated with improved long-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
4
16
0
Order By: Relevance
“…Another concern regarding rituximab use in children with NS is the lack of long term safety data. The use of multiple courses over multiple years in the same child have been reported by studies at the time of relapses and/ or the time of CD count recovery with no reported significant side effects (31, 36, 42, 52, 57, 100, 131). However, it is not yet known how many doses can be considered safe in children with NS.…”
Section: Side Effects Of Rituximabmentioning
confidence: 85%
See 1 more Smart Citation
“…Another concern regarding rituximab use in children with NS is the lack of long term safety data. The use of multiple courses over multiple years in the same child have been reported by studies at the time of relapses and/ or the time of CD count recovery with no reported significant side effects (31, 36, 42, 52, 57, 100, 131). However, it is not yet known how many doses can be considered safe in children with NS.…”
Section: Side Effects Of Rituximabmentioning
confidence: 85%
“…Children with SDNS or FRNS, and especially those with SRNS whose disease is difficult to control, are often continued on various doses of other immunosuppressive agents such as MMF or CNIs to try to maintain them in remission and decrease the rate of relapses (97100). In this context, there is currently a multicenter randomized trial underway to test the benefit of using MMF following rituximab therapy in children with FRNS or SDNS (101).…”
Section: Factors That May Affect the Clinical Response Of Rituximab Imentioning
confidence: 99%
“…Fujinaga et al (16) studied the predictors of relapse and long-term outcome in 43 SDNS patients given a single dose of RTX as induction treatment. In all, 91% of their patients relapsed.…”
Section: Discussionmentioning
confidence: 99%
“…Fujinaga reported 24-month relapse rates on a low-dose regimen, reporting 91% relapse (39 patients) at a median of 586 days [28]. Greater risk of relapse was associated with younger age of administration and more rapid reconstitution of B cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…Greater risk of relapse was associated with younger age of administration and more rapid reconstitution of B cells [28]. …”
Section: Discussionmentioning
confidence: 99%